2018
DOI: 10.1097/ftd.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag-Induced Acute Liver Failure in a Pediatric Patient: A Pharmacokinetic and Pharmacogenetic Analysis

Abstract: Eltrombopag is an oral thrombopoietin receptor agonist approved for the treatment of patients with chronic idiopathic thrombocytopenic purpura (ITP), who are more than 1 year old, and show poor response to first-line therapy. ITP is a hematological disorder characterized by isolated thrombocytopenia in the absence of secondary causes or disorders. Eltrombopag is generally well tolerated in the pediatric population; therefore, therapeutic drug monitoring (TDM) is not usually performed in clinical practice.We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This may be due to the short timeframe of this study, because we only analyzed inpatient data, not follow-up data. It was reported that a 3-year-old patient with chronic ITP developed acute liver failure due to eltrombopag toxicity (15). A very high eltrombopag plasma concentration was found despite taking the standard drug dosage,and allelic variations that are involved in drug metabolism [CYP2C8 and UDP glucuronosyltransferase (UGT) 1A1 (UGT1A1)] were carried in this patient.…”
Section: Discussionmentioning
confidence: 78%
“…This may be due to the short timeframe of this study, because we only analyzed inpatient data, not follow-up data. It was reported that a 3-year-old patient with chronic ITP developed acute liver failure due to eltrombopag toxicity (15). A very high eltrombopag plasma concentration was found despite taking the standard drug dosage,and allelic variations that are involved in drug metabolism [CYP2C8 and UDP glucuronosyltransferase (UGT) 1A1 (UGT1A1)] were carried in this patient.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, this patient demonstrated absence of elevated transaminases until well after hepatic and neurological symptoms developed. Notably, Marano et al8 reported a similar case involving a 3-year-old child suffering from chronic ITP with CYP2C8 variants who developed hepatic and neurological sequelae as a result of eltrombopag toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, rebound thrombocytopenia is a known risk of abrupt TPO-RAs discontinuation. 10,11 However, because of the relatively recent wide use of this molecule, possible long-term effects of TPO-RAs are still unknown; this is particularly concerning when treating very young children.…”
Section: Immune Thrombocytopenia In Two Infant Cases Managed With Eltrombopagmentioning
confidence: 99%